Coronary angiography in patients undergoing carotid artery stenting shows a high incidence of significant coronary artery disease. Issue 11 (10th March 2005) - Hofmann, R; Kypta, A; Steinwender, C; Kerschner, K; Grund, M; Leisch, F
Abstract : Objective: To assess the incidence, morphology, and associated clinical symptoms of coronary artery disease in patients undergoing elective carotid artery stenting. Methods: In a prospective observational study at a tertiary care centre (university teaching hospital) 444 consecutive patients underwent elective stenting of the carotid artery. Twenty four patients had to be ruled out because of urgent carotid intervention for severe neurological symptoms, lack of compliance, complications from vascular puncture, or renal failure. In 390 patients, the coronary angiography was performed together with carotid artery stenting in a single session; the remaining 30 patients have had a recent coronary angiography. Results: One, two, and three vessel disease and left main stenoses were found in 70 (17%), 64 (15%), 93 (22%), and 31 (7%) patients, respectively. Sixty six (16%) patients had a history of coronary artery disease but no current significant stenosis. Only 39% of the patients with significant stenoses (n  =  258) had clinical cardiac symptoms. Conclusions: For patients undergoing elective stenting of the carotid, routine coronary angiography reliably discloses morphologically significant coronary artery disease and enables consecutive treatment in 61% and 29%. This safe measure is useful because a majority of patients with a significant stenosis are asymptomatic.